2013
DOI: 10.1128/jcm.00622-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Next-Generation Digital PCR Diagnostic Assay for Ocular Chlamydia trachomatis Infections

Abstract: Droplet digital PCR (ddPCR) is an emulsion PCR process that performs absolute quantitation of nucleic acids. We developed a ddPCR assay for Chlamydia trachomatis infections and found it to be accurate and precise. Using PCR mixtures containing plasmids engineered to include the PCR target sequences, we were able to quantify with a dynamic range between 0.07 and 3,160 targets/μl (r2 = 0.9927) with >95% confidence. Using 1,509 clinical conjunctival swab samples from a population in which trachoma is endemic in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
125
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 47 publications
0
125
0
1
Order By: Relevance
“…Because absolute quantification and enhanced detection sensitivity can be achieved, ddPCR has been used in various research applications, such as in microorganism detection 12 and biomedical research. 3 In our study, a specific and sensitive diagnostic method based on ddPCR for the detection of PCV-2 was established.…”
mentioning
confidence: 99%
“…Because absolute quantification and enhanced detection sensitivity can be achieved, ddPCR has been used in various research applications, such as in microorganism detection 12 and biomedical research. 3 In our study, a specific and sensitive diagnostic method based on ddPCR for the detection of PCV-2 was established.…”
mentioning
confidence: 99%
“…Several studies have previously investigated the potential of droplet digital PCR (ddPCR) in molecular diagnostics for pathogens, including assays for chlamydia (8), HIV (9, 10), CMV (11), and chromosomally integrated human herpesvirus 6 (HHV-6) (12). In the previous CMV study, investigators concluded that quantitative PCR showed greater sensitivity and less variability than ddPCR in clinical samples (11).…”
mentioning
confidence: 99%
“…However, we suggest for the reasons outlined below that the sensitivity estimates presented in our evaluation are likely misleading. The issues behind calculating sensitivity in ddPCR and the reasons why this appeared 'low' given the technical superiority of digital PCR have been discussed [1,3]. The low sensitivity that we reported is most likely explained simply by sampling error, which is a problem that is unavoidable at low analyte concentrations in any test system [4], as reported by Schachter et al in 2006 [5].…”
Section: Sensitivitymentioning
confidence: 57%
“…Julius Schachter offers a provocative title in his expert review of the diagnostic Chlamydia trachomatis droplet digital PCR (CT ddPCR) assay developed by Roberts et al [1,2]. He put forward four main objections to the utility of this test in the face of other next-generation commercial nucleic acid amplification test platforms.…”
mentioning
confidence: 99%